Laboratory Study of the Effect of Cement Stabilization of the Interface of Reinforcement and Sand on the Interface Shear Strength - Eliar Heidarli; Ahad Ouria (پژوهش‌های زیرساخت‌های عمرانی, 2023)
In this study, the effects of the cement stabilization on the interface of the soil and a geotextile, the thickness of the cement and geotextile layer, and the thickness of the geotextile layer on the interface shear strength have been investigated experimentally. In the experiments, a direct shear device with a cylindrical mold with a diameter of 6 cm was used. The geotextile was a woven type. The cement-treated reinforcements were papered by the application of a thin layer of cement with amounts of 0.016, 0.048, 0.08, and 0.112 gr/cm2 on the surface of saturated geotextiles. Geotextiles with different thicknesses were produced by joining several layers of geotextiles using a flexible glue. The interface shear tests have been performed under vertical stresses of 50, 100, and 150 kPa. The results show that adding 0.112 grams/cm2 of cement to the interface of the reinforcements can increase the shear strength of the interface of the samples by 50%, but the amount of cement added should not be less than a certain limit. By comparing the results of tests conducted with different thicknesses of reinforcement with different amounts of cement, it can be concluded that increasing both the cement content and the thickness of the reinforcement increases the shear strength of the interface. By increasing the thickness of the reinforcement, the soil grains are integrated into the reinforcing fabric, produce a rough surface, and increase the shear strength at the interface of the soil and the geotextile.